Best Answer

Anything multiplied by 0 is 0, so all the ones before the 0 can be ignored. It is now 0+1 which equals 1.

User Avatar

Wiki User

โˆ™ 2016-07-29 13:51:40
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What is 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 x0 plus 1?
Write your answer...
Related questions

What is the answer to Evaluate x1 - x-1 plus x0 for x equals 2?

shut up and do your hw

The measure of the supplement of an angle exceeds twice the measure of the supplement of the complemant of the angle by 40?

The answer is -13 1/3ohere is the detailed calculation for the problem:Let x0 be the angle, then;(180 - x0) - 2[180 - (90 - x0)] =40(180 -x0) - 2[90+x0]=40180 -x0 - 180 - 2x0=40-3x0=40hencex0= -13 1/3oAny comments are welcome

When x0 how many solutions is this?

x0 = 1 because any number raised to the power of 0 is always equal to 1

What is the C plus plus program for regula falsi method?

#include#include#include#includefloat eq(float);void falsi(float,float,int);void main(){float x0,x1;int iter;clrscr();cout

Equation for linear approximation?

The general equation for a linear approximation is f(x) ≈ f(x0) + f'(x0)(x-x0) where f(x0) is the value of the function at x0 and f'(x0) is the derivative at x0. This describes a tangent line used to approximate the function. In higher order functions, the same concept can be applied. f(x,y) ≈ f(x0,y0) + fx(x0,y0)(x-x0) + fy(x0,y0)(y-y0) where f(x0,y0) is the value of the function at (x0,y0), fx(x0,y0) is the partial derivative with respect to x at (x0,y0), and fy(x0,y0) is the partial derivative with respect to y at (x0,y0). This describes a tangent plane used to approximate a surface.

What is X to the 0 power over x to the -5 power?


What is 1 over x0 equal?

x^0 = 1 1/1 = 1

How the results of 0x1 2-1 x0?

In order to get the results of 0x1*2-1*x0 you will have to do a little math. The answer to this math problem is X equals one.

Fortran program code for newton raphson method?

Function f(x) x2=x*x f=x*x2-3*x2+2*x-1 return end function f1(x) f1=3*x*x-6*x+2 return end 5 write(*,*)'enter initial guess' read(*,*) x0 write(*,*)'enter tolerrence' read(*,*) eps 10 x1=x0-f(x0)/f1(x0) if(abs((x1-x0)/x0).lt.eps) then write(*,1) x1 1 format('solution=',f10.4) stop else x0=x1 go to 10 endif end

What does seven to the zero power equal?

Zero. x0 = 1.

How do you integrate of e -2x for x0?

The integral of e-2x is -1/2*e-2x + c but I am not sure what "for x0" in the question means.

Display the following equation in your page -344x plus 54x3 plus 62x2 plus 2x0 equals 0?

most commonly you would place the highest exponent first. x0 = 1. 54x3 + 62x2 - 344x + 2 = 0

Why is 10 power 0 equal to 1?

Any number to the power zero is equal to one. That can be derived from the following index law: xa*xb = xa+b (x not zero) Now let b = 0 so that the above becomes xa*x0 = xa+0 so xa*x0 = xa (since a+0 = a) That is, any number multiplied by x0 is the number itself. That can be true only if x0 is the multiplicative identity, that is, only if x0 = 1.

What is the answer for x0 for the function y12x plus 88?

If x is zero, then y12x is also zero. The answer is therefore 88.

What is Newton raphson's method in r programing?

It's a method used in Numerical Analysis to find increasingly more accurate solutions to the roots of an equation. x1 = x0 - f(x0)/f'(x0) where f'(x0) is the derivative of f(x0)

Why does x to the 0 power equal 1?

x3 = x times x times x x0 = x divided by x ---- (another explanation) x0 = 1 provided x in not 0 because this definition is consistent with all other definition of exponents. The easiest is the rule for multiplying powers of a like base by adding the exponents: (xp)(xq) = xp+q Suppose q = 0 and you apply the rule to get (xp)(x0) = xp+0 = xp (1) . Cancel xp from both sides and get x0 = 1. Another rule says to divide powers, subtract the exponents: (xp)/(xq) = x p-q Suppose you apply the rule when p = q: You get (xp)/(xp) = x p-p = x0. But xp/xp = 1 so x0 must be 1. A more complicated reason is that the limit as x goes to infinity of x(1/n) is 1. so it makes sense to define x0 = 1.

What is the net displacement of the particle between 0 seconds and 80 seconds?

That would besqrt[ (x80 - x0)2 + (y80 - y0)2 ) at an angle of tan-1 (y80 - y0) / (x80 - x0)or(x80 - x0) i + (y80 - y0) j

10 to the power of 0?

1 anything to the power of 0 equals 1 100=1 x0=1

Why does a number with a 0 expont euqal 0?

In fact, a non-zero number with an exponent of 0 is always equal to 1. This can be explained with a simple example. Let x = 2. x2=4 x2=4 Thus it follows: x2 / x2 = x0 And thus: x0 = 4 / 4 4 / 4 = 1 Therefore x0=1.

What do you put for exponets of 1?

1 = x0 where x is any non-zero real number.

Why does everything to the 0 power 1?

The multiplicative law of indices states that xa * xb = xa+b Now, if you put b = 0 in that equation you get xa * x0 = xa+0 But a+0 = a so the right hand side is simply xa Which means, the equation becomes xa * x0 = xa This is true for any x. That is, multiplying any number by x0 leaves it unchanged. By the identity property of multiplication, there is only one such number and that is 1. So x0 must be 1.

Why any number raised to power zero is 1?

This derives from one of the laws of indices which states that, for any x (not = 0), xa * xb = xa+b Put b = 0 Then xa * x0 = xa+0 = xa (because a + 0 = a) But that means that x0 is the multiplicative identity. And since that is unique, and equal to 1, x0 = 1. This is true for all x. Put

Why a number to the zero power is always equal to 1?

It is a consequence of the definition of the index laws. xa * xb = xa+b If you put b = 0 in the above equation, then you get xa * x0 = xa+0 But a+0 = a so that the right hand side becomes xa Thus the equation now reads xa * x0 = xa For that to be true for all x, x0 must be the identity element for multiplication. That is x0 = 1 for all x.

What is the zero exponent property?

Any number to the exponent of 0 is equal to 1. EXAMPLE x0=1

What is the slope of the line joining 2 0 and 1 3?

between points (x0, y0) and (x1, y1): slope = change_in_y/change_in_x → slope = (y1 - y0)/(x1 - x0) → slope = (3 - 0)/(1 - 2) = 3/(-1) = -3